Farm Protection System for Animal and Human Theft Using Solar Photovoltaic-Powered IoT System - Khalid, Izzah Khalidah; Mohammad Radzi, Nur Hanis (Evolution in Electrical and Electronic Engineering, 2024)
The agricultural sector in Malaysia plays a vital role in producing food and raw materials, significantly contributing to the country's economic well-being. However, this sector faces several issues, including weather fluctuations, declining soil quality, and wildlife attacks. Farmers may sustain large financial losses as a result of this damage, which can drastically lower crop output. The primary concern is the direct harm to crops, which leads to lower yields and financial difficulties. The aim is to design and develop an Internet of Things (IoT)-based protection system that can monitor unauthorized access or potential threats from animals and humans at any time. The project utilized the Blynk IoT platform to create a custom application for monitoring and controlling the protection system. The system itself incorporates motion sensors and alarms. Farmers will receive real-time notifications through the Blynk app. The system integrates several components such as Passive Infrared (PIR) sensors, a buzzer, a Light Dependent Resistor (LDR), and a light-emitting diode  (LED). It is powered by solar photovoltaic (PV) technology, ensuring sustainability and environmental friendliness. When the system detects a motion, it triggers the buzzer, enabling farmers to improve security and reduce losses. The maximum detection range is up to 12 meters. This innovative technology offers constant security and monitoring without depending on traditional power sources by utilizing solar energy in the system.